Tiktok as a tool for education in undergraduate studies / Mohamed Faizal Sikkandar... [et al.] - Sikkandar, Mohamed Faizal; Mohd Miswan, Mohd Fairudz; Yahaya, Mohd Yusoff; Sulaiman, Shahrul Hisham (UiTM Perak Press, 2022)
Social media is a popular form of entertainment for the public even since the pre-pandemic era. Facebook, Twitter and Tiktok seem to be the popular choice of communication among students, as the content in these media are updated often to keep up with the current times. Even professionals like doctors in hospital clinical practice, use the Whatsapp communication system to share updates and information among themselves on their treated patients. Many Whatsapp groups are formed to disseminate shared information and educate the group members on common interests and ideas. In this paper, we would like to highlight the importance and advantages of using social media as an adjunct to educate undergraduate students and make their studies creative and informative at the same time. This paper highlights the benefit of using the specific social media Tiktok to educate undergraduate students and create a creative and conducive environment for transfer of knowledge.